2023
DOI: 10.1038/s41598-023-40429-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of monocyte-to-lymphocyte ratio for 90-day all-cause mortality in type 2 diabetes mellitus patients with chronic kidney disease

Abstract: The role of inflammation and the correlation between inflammatory markers and type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD) have been studied. In clinical work, a large number of T2DM patients complicated with CKD, but the cause of CKD was not clear. Our study aimed to evaluate the relationship between monocyte-to-lymphocyte ratio (MLR) and mortality in T2DM patients with CKD. The data from Medical Information Mart for Intensive Care III was analyzed. The primary outcome was 90-day all-cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In our study, patients with DFU had a significant high MLR and incidence of DFU increases with MLR. This is similar to the research on MLR in other diabetes complications ( 7 , 22 24 ). For example, Yue et al.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our study, patients with DFU had a significant high MLR and incidence of DFU increases with MLR. This is similar to the research on MLR in other diabetes complications ( 7 , 22 24 ). For example, Yue et al.…”
Section: Discussionsupporting
confidence: 88%
“…The onset of diabetes and its associated problems are mostly influenced by pathophysiological circumstances, including inflammation, endothelial dysfunction, ferroptosis and procoagulant imbalance ( 26 28 ). These pathophysiological processes interact with metabolic and inflammatory problems in patients with diabetes, causing tissue damage and ultimately leading to consequences, such as PAD, retinopathy, neuropathy, and nephropathy ( 28 ).According to several studies, changes in inflammatory biomarkers has been confirmed to be closely related to the occurrence and progression of diabetic complications ( 7 , 22 24 ). These biomarkers may provide new insights for the early detection and treatment of diabetes and its consequences ( 27 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One biomarker that helps forecast how CKD will progress is the neutrophil-to-lymphocyte ratio (NLR) ( 8 ). Monocyte-to-lymphocyte ratio (MLR) and the risk of 90-day all-cause death in patients with type 2 diabetes (T2DM) and diabetic kidney disease (DKD) were found to be significantly correlated by Qiu’s research ( 9 ). Monocyte/high-density lipoprotein ratio (MHR) may be a biomarker for predicting DKD ( 10 ).…”
Section: Introductionmentioning
confidence: 99%